Carbon pillars power microbatteries. - Das, S.R (IEEE spectrum)
Pillars of Power- Microscopic pillars of carbon form the electrodes in a University of California, Irvine, microbattery. Groups of pillars can be connected to the battery circuit individually so the amount of current generated can be precisely controlled.